Analisis Wacana Linguistik Dan Semiotika Teks Keislaman - Muntako .; Kholid Mawardi (CV. ITTC INDONESIA, 2025)
This study aims to analyze Islamic texts through linguistic discourse analysis and semiotic approaches in order to reveal their linguistic structures, sign systems, and meaning constructions. The research employs a qualitative approach with a library research design. The data consist of Islamic texts, including the Qur’an, Hadith, as well as classical and contemporary Islamic writings, which are analyzed using a descriptive-interpretative method. Linguistic discourse analysis is applied to examine lexical choices, rhetorical strategies, discourse framing, cohesion, coherence, and intertextuality, while semiotic analysis focuses on symbolic meanings through the relationships between signs, denotation, and connotation. The findings indicate that Islamic texts are constructed through normative and persuasive language that represents particular religious ideologies and authorities. Religious symbols within Islamic texts contain multilayered and contextual meanings that dynamically evolve in response to social and media changes. The integration of linguistic discourse analysis and semiotics provides a more holistic understanding of Islamic texts as living and dynamic discourses interacting with social realities. This study highlights the importance of interdisciplinary approaches in Islamic textual studies to foster critical, contextual, and relevant interpretations in contemporary Muslim societies.